Anastomotic techniques for oesophagectomy for malignancy: systematic review and network meta‐analysis. Issue 4 (23rd May 2020) - Kamarajah, S. K.; Bundred, J. R.; Singh, P.; Pasquali, S.; Griffiths, E. A.
Abstract : Background: Current evidence on the benefits of different anastomotic techniques (hand‐sewn (HS), circular stapled (CS), triangulating stapled (TS) or linear stapled/semimechanical (LSSM) techniques) after oesophagectomy is conflicting. The aim of this study was to evaluate the evidence for the techniques for oesophagogastric anastomosis and their impact on perioperative outcomes. Methods: This was a systematic review and network meta‐analysis. PubMed, EMBASE and Cochrane Library databases were searched systematically for randomized and non‐randomized studies reporting techniques for the oesophagogastric anastomosis. Network meta‐analysis of postoperative anastomotic leaks and strictures was performed. Results: Of 4192 articles screened, 15 randomized and 22 non‐randomized studies comprising 8618 patients were included. LSSM (odds ratio (OR) 0·50, 95 per cent c.i. 0·33 to 0·74; P  = 0·001) and CS (OR 0·68, 0·48 to 0·95; P  = 0·027) anastomoses were associated with lower anastomotic leak rates than HS anastomoses. LSSM anastomoses were associated with lower stricture rates than HS anastomoses (OR 0·32, 0·19 to 0·54; P  < 0·001). Conclusion: LSSM anastomoses after oesophagectomy are superior with regard to anastomotic leak and stricture rates. Abstract : Stapled anastomoses were associated with lower anastomotic leak rates than hand‐sewn anastomoses following oesophagectomy. Furthermore, linear stapled/semimechanical (LSSM) techniques were associated with lower rates of anastomotic stricture than circular stapled or hand‐sewn anastomoses. Current evidence therefore suggests superiority for the LSSM technique for oesophagogastric anastomosis. Linear stapler techniques superior Abstract : Antecedentes: La evidencia actual sobre los beneficios de diferentes técnicas de anastomosis, incluyen la técnica manual ( hand‐sewn, HS), la sutura mecánica circular ( circular stapled, CS), la sutura mecánica triangular ( triangular stapler, TS) o la sutura mecánica lineal/semi‐mecánica ( linear stapler/semi‐mechanical ., LSSM) tras una esofaguectomía es contradictoria. El objetivo de este estudio fue evaluar la evidencia referente a las técnicas de anastomosis esofagogástrica ( oesophagogastric, OG) y su impacto sobre los resultados perioperatorios. Métodos: Se efectuó una revisión sistemática y metaanálisis en red, basados en una búsqueda sistemática en las bases de datos PubMed, EMBASE y Cochrane Library de estudios aleatorizados y no aleatorizados que describiese técnicas para la anastomosis OG. Se llevó a cabo un metaanálisis en red para los resultados de fugas anastomóticas y estenosis postoperatorias. Resultados: De los 4.192 artículos revisados, se incluyeron 15 estudios aleatorizados y 22 no aleatorizados con un total de 8.618 pacientes. Las anastomosis con LSSM (razón de oportunidades, odds ratio, OR 0, 49, i.c. del 95%: 0, 33‐0, 74, P = 0, 001) y las anastomosis con CS (OR 0, 68, i.c. del 95%: 0.48‐0, 95, P = 0, 027) se asociaron con tasas de fugas anastomóticas más bajas que las anastomosis con HS. Las anastomosis con LSSM se asociaron con unas tasas más bajas de estenosis (OR 0, 15, i.c. del 95%: 0, 08‐0, 28, P < 0, 001), frente a las anastomosis con TS y HS. Conclusiones: Las anastomosis con LSSM después de esofaguectomía son superiores en relación a las tasas de fugas anastomóticas y estenosis.